2007 IEEE Sensors 2007
DOI: 10.1109/icsens.2007.4388479
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensors from Lead Metallophthalocyanine Whiskers

Abstract: Lead phthalocyanine (PbPc) single crystal whiskers were grown in vacuum via physical vapor deposition technique. The individual whiskers were used as gas-sensing elements of the conductometric gas sensing devices. These chemiresistors were found to respond sensitively and selectively to NO 2 . High crystallinity and high surface to bulk ratio determine the advantageous stability and time response characteristics of such sensing elements in comparison with polycrystalline films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other recent PTIR innovations include the extension to the visible spectral range 35 and operation in a water environment. 37,38 Due to these characteristics, PTIR impacts an ever-growing number of applications including, polymer science, 39,40 photovoltaics, 41,42 plasmonics, 43,44 geology, 45 biology, 46 and medicine, 47,38,36 as discussed in recent reviews. 26,27 For 2D materials, PTIR has been applied to characterize the polariton distribution in hBN nanostructures 48,49 and to characterize the functional groups in graphene oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Other recent PTIR innovations include the extension to the visible spectral range 35 and operation in a water environment. 37,38 Due to these characteristics, PTIR impacts an ever-growing number of applications including, polymer science, 39,40 photovoltaics, 41,42 plasmonics, 43,44 geology, 45 biology, 46 and medicine, 47,38,36 as discussed in recent reviews. 26,27 For 2D materials, PTIR has been applied to characterize the polariton distribution in hBN nanostructures 48,49 and to characterize the functional groups in graphene oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a,b shows the particles of complex 2 and complex 3 by scanning electron microscopy (SEM), with a whiskers-like morphology and crystal shape characteristic typical of the triclinic space group [37]. For both cases, the SEM images and the non-symmetric unimodal graphics for the dispersion of sizes, revealed that the whiskers tend to be smaller in the longitudinal direction, varying from 1.0 µm to 2 µm with a median longitudinal particle size (d 50 ) of 6.7 µm and longitudinal particle size distribution d 80 of 11.1 µm for the complex 2.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Improved understanding of ionic transport and reactions will impact the work not only on traditional lithium ion batteries but also the broader space of electrochemically active systems including fuel cells 2 and resistive switching devices. 3,4 In recent years, several techniques for studying electrochemical systems at the nanoscale have been developed using scanning-probe microscopy (SPM) tip-based methods [5][6][7][8][9][10][11] and electron microscopy based techniques. [12][13][14][15][16][17] These techniques have been used to explore nanoscale electrochemistry by driving reactions through nanostructures or through use of SPM conductive tips as electrodes.…”
mentioning
confidence: 99%
“…3,4 In recent years, several techniques for studying electrochemical systems at the nanoscale have been developed using scanning-probe microscopy (SPM) tip-based methods [5][6][7][8][9][10][11] and electron microscopy based techniques. [12][13][14][15][16][17] These techniques have been used to explore nanoscale electrochemistry by driving reactions through nanostructures or through use of SPM conductive tips as electrodes. In the lithium-silicon system, this approach has enabled the observation of atomically-thin lithiation phase fronts and detailed studies of phase-front dynamics under strain.…”
mentioning
confidence: 99%